Satyagraha as a Mass Movement in India: - (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The reasons for which Gandhi chose the techniques of Swadeshi, Satyagraha, non-cooperation, picketing and boycott of foreign goods as opposed to open armed insurgency, must be examined in the context of the Indian socio-cultural ethos and the history of Indian freedom struggle. The historic- political situation combined with the rich tradition which produced nonviolent religions philosophical systems like Buddhism and Jainism gave rise to Satyagraha. In YOUNG INDIA (24th Nov, 1921) Gandhi wrote The people are too peaceful to stand anarchy. They will bow the knee to anyone who restores so called order. Let us recognise the Indian psychology. We need not stop to inquire whether such hankering after peace is a virtue or a vice. The average Mussalman of India is quite different from the average Mussalman of the other parts of the world. His Indian associations have made him more docile than his co-religionists outside India. He will not stand tangible insecurity of life and property for any length of time. The Hindu is proverbially, almost contemptibly, mild. The Parsi and Christian love peace more than strife. Indeed, we have almost made religion subservient to peace. This mentality is at once our weakness and our strength. In this research work, I will highlight satyagrah’s characteristics which made it mass movement.